Comparative Analysis of the Histology of the Hypothalamus in Albino Rats (Rattus albus) and Wild Brown Rats (Rattus norvegicus) (Indian Journal of Animal Production and Management, 2025)
Objectives: This study investigates the histological structure of the hypothalamus in  wild and albino rats, highlighting significant differences in their cellular composition  and organization. Methods: twelves’ healthy rabbits, and all experimental animals  have been adapted in the animal house. The current study includes comparative  examinations between two types of animals that were divided into two groups: wild  and albino rats, (6 animals for each group). The routine stained used (Haematoxylin  and Eosin Staining). Results: The hypothalamus of wild rats is composed of many  nuclei organized into discrete areas, each of which carries out specific tasks. with the  anterior part of the hypothalamus having a greater concentration of nuclei. While  glial cells are less common in wild animals, the majority of neurons in wild rats are  multipolar, have long axons, and have a rich cellular structure that highlights the  hypothalamus. The hypothalamus of albino rats, on the other hand, has larger nuclei,  which are clustered in the posterior region. Compared to wild rats, these nuclei have  a lower blood supply and are made up of thinner and smaller neurons. These cells’  cellular distribution and arrangement imply that the hypothalamus of albino rats  supports a wider variety of functions than that of other species. Important anatomical  differences between the hypothalamus of wild and albino rats are further highlighted  by the fact that albino rats have a higher number of glial cells, particularly astrocytes,  which are scattered and mixed with the neuropil. Conclusion: According to the  histological comparative study, the hypothalamus of the two rat species differed  greatly, depending on their diets and behaviors.
Keywords: Hypothalamus; comparative study; wild rats